P80 Rebound in asthma exacerbations following relaxation of COVID-19 restrictions. (11th November 2022) - Tydeman, F; Martineau, A; Pfeffer, P
Abstract : Introduction: The imposition of COVID-19 restrictions in Spring 2020 was followed by a drop in asthma exacerbations in the UK. 1 Temporal trends in asthma exacerbations following relaxation of these restrictions have not yet been described. Objectives: To describe temporal trends in use of face coverings, social mixing, incidence of acute respiratory infections (ARI) and risk of exacerbations in a UK cohort of adults with asthma between November 2020 and April 2022. Methods: Participants (n=2740) were adult UK residents with doctor-diagnosed asthma who took part in a national population-based longitudinal study of COVID-19 (COVIDENCE UK). Details of face covering use, social mixing, and incidence of RT-PCR- or antigen test-confirmed COVID-19, non-COVID ARI (RT-PCR- or antigen test-negative for SARS-CoV-2) and moderate/severe asthma exacerbations (i.e. those requiring treatment with systemic corticosteroids and/or hospitalisation) were collected via monthly on-line questionnaires. Changes in these parameters over time were visualised using generalised additive models. Multivariate mixed logistic regression was used to calculate adjusted odds ratios (aOR) for associations between incident ARI and risk of asthma exacerbations, adjusting for age, sex, ethnicity, sociodemographic factors, self-rated health, asthma severity and asthma exacerbation history prior to enrolment. Results: COVID-19 restrictions were relaxed between April and December 2021. This period coincided with reduced use of face coverings (p<0.001), increased frequency of indoor visits to public places and other households (p<0.001) and rising incidence of COVID-19 (p<0.001), non-COVID ARI (p<0.001) and asthma exacerbations (p=0.006; figure 1 ). After adjustment for multiple potential confounders, incident non-COVID ARI associated with an increased risk of asthma exacerbation (aOR 7.04, 95% CI 5.73 to 8.65), as did incident COVID-19, both prior to emergence of the omicron variant of SARS-CoV-2 in December 2021 (aOR 5.56, 95% CI 2.85 to 10.81) and subsequently (aOR 6.73, 95% CI 4.59 to 9.85). Conclusions: Relaxation of COVID-19 restrictions coincided with decreased use of face coverings, increased social mixing and a rebound in ARI and asthma exacerbations. Associations between incident ARI and risk of exacerbation were similar for non-COVID ARI and COVID-19, both before and after emergence of the omicron variant of SARS-CoV-2. Reference: Thorax, 2021. 76 (9): p. 867–873. Please refer to page A214 for declarations of interest related to this abstract.